Biopsychosocial approach and Burnout Syndrome: in search of the association of constructs - Brito, Lucas Charão; Silva, Andressa Hennig; Lopes, Luis Felipe Dias; Moura, Gilnei Luiz de (Revista de Administração da UFSM, 2016)
Under the context of rationality, the way work is organized can trigger incompatibilities between the spheres of the motivations, achievements and wishes of individuals, taking it well, the loss of the sense and following injuries in the physical and mental health worker (DEJOURS, 2006). Given this context, this study was conducted in order to identify possible relationships between the Biopsychosocial Approach to Quality of Life at Work (QVT) and the Burnout Syndrome. The sample relates to a survey of 575 professionals from public and private organizations in a municipality in Region / BR. Data were analyzed using analysis: descriptive analysis and correlation factor. The main results shows that professionals dissatisfied with the QWL programs are more prone in the development of burnout syndrome.